Productivity of Vannamei Shrimp Litopenaeus vannamei in Intensive Aquaculture System with the Addition of Probiotics at CV. Daun Prima, East Java - Pratiwi, Rifqah; Tangguda, Sartika; Raditya, Made Saha Apta (Management Science Research Journal, 2023)
Vannamei shrimp Litopenaeus vannamei is one of the leading fishery commodities that have high economic value. The very high market demand for vannamei shrimp makes farmers carry out intensive cultivation with the addition of probiotics, in order to produce high productivity. This study aims to determine the productivity of vannamei shrimp in intensive cultivation with the addition of probiotics. This research method is a case study that includes interviews, observations, and following all stages in the process of vannamei shrimp production at CV. Daun Prima. Techniques of vannamei shrimp cultivation include pond preparation, media preparation, fry selection and stocking, feed management, water quality management, growth monitoring, pest and disease monitoring, and harvesting. The treatment used is the administration of probiotics containing bacteria Bacillus sp., Lactobacillus sp., Nitrosomonas, and Nitrobacter which function to optimize shrimp growth and maintain stable water quality. Shrimp production performance during 77 days of maintenance yielded SR 87%; biomass 2.8 tons; harvest size 66; ABW 15.15 grams/ind; ADG 0.23 grams/day; and FCR 1.12. Water quality during maintenance is within the optimum range to support shrimp growth, including temperature 28 – 31 °C; brightness 22 – 44 cm; pH 7.6 – 8.4; salinity 30 – 32 g/L; and dissolved oxygen 4.4 – 5.3 mg/L. Vaname shrimp cultivation with intensive technology with the addition of probiotics applied at CV. Daun Prima shows optimal productivity.